(untitled) (Research, Society and Development, 2023)
Objective: Accordingly, the objective of this study was to analyze the profile of women who underwent mammography in Brazil in the period of 2013 to 2021. Methodology: The research universe was the database of the Cancer Information System (SISCAN), referring to the records of patients who underwent screening mammography in Brazil, in the period between 2013 and 2021. Furthermore, the analysis of the collected data was performed using Excel software (Microsoft Office ® 2019). Results: In the period researched, 19,188,002 mammograms were registered, with the highest number, 3,063,618, performed in 2019. We highlight the North and Midwest regions where there was a discordant number in relation to the predominant age group and that recommended by the Ministry of Health. An increasing pattern of mammograms was observed in all regions. In contrast with all the years analyzed, it was observed that in the year 2020 there was a decrease in the number of exams performed, presumably related to the COVID-19 pandemic. Conclusion: The results of this study revealed, in general, that the age range comprised in women who perform screening mammography is 40 to 59 years, and that the gap between examinations is predominantly 01 year. We emphasize the importance of the correct and complete collection of the patients’ registration data, due to a better epidemiological and social tracing of the women who undergo screening mammography.